INVESTIGASI KARAKTERISTIK HAMBATAN PENTAMARAN BENTUK LAMBUNG WIGLEY DAN CHINE DENGAN MENGGUNAKAN CFD - Wiwin Sulistyawati (Bina Teknika, 2017)
Several studies of multi-hulls ship showed that hull resistance could be predicted from position between the each hull. The design optimization of the hull form could be considered by minimizing resistance, which is generally the sum of the viscous resistance and the wave making resistance of the ship model. This paper presents an investigation of pentamaran hull form with chine hull form to the effects of outriggers position, asymmetry, and deadrise angles on the resistance characteristics. This research investigated the resistance characteristics by modeling pentamaran hull form using chine with symmetrical main hull and asymmetric outboard on the variation deadrise angles: 25o, 30o, 35o and Froude number 0,1 to 0,7. We examined the calm water resistance characteristics of six pentamaran models with chine-hull form by variation of deadrise angles using Ansys CFD. Increasing the deadrise angle of chine hull form contribute to the resistance due to the interaction of the wave systems produced by each demihull. Strong interaction effect on the resistance coefficient component was found for change in the hull length as well. Compared to the wigley hull form, the maximum drag reduction of the chine hull form was reduced by 18.05% in deadrise 250, 16.1% in deadrise 300, and 18.19% in deadrise 350. While the smallest value of total resistance coefficient was generated from chine 350 at R/L:1/14 and R/L:1/7. Optimum hull form for minimum resistance has been obtained, so it is interesting to continue with angle of entrance and stem angle of hull for further research.